Effect of variety on nutritive value and anti-methanogenic potential of oat grain - kurt, özer (Progress in Nutrition, 2021)
The objective of the study was to evaluate effect of variety on chemical composition, in vitro gas production, methane production, metabolisable energy (ME), organic matter digestibility (OMD) of oat grain.  Variety had on chemical composition, in vitro gas production, methane production, ME, OMD of oat grain. Crude protein contents of oat varieties ranged from 9.30 to 12.65% with the highest values in TL293 and the lowest in Arslanbey. NDF and ADF contents of oat varieties ranged from 33.21 to 45.57% and 14.10 to 17.31 % respectively. NDF content of Variety of TL 258 was significantly higher than the others whereas ADF content of variety of Checorta was significantly higher than the others.  GP and MP ranged from 49.70 to 58.01 ml, 7.72 to 10.18 ml. The GP from TL 80, Arslanbey and Faikbey were significantly higher than the others whereas methane production from variety of TL 304 was significantly lower than the others. The percentage of CH4 of oat grain ranged from 15.20 to 17.60%. ME and OMD of oat grains from different varieties ranged from 10.46 to 12.03 MJ (kg /DM) and 71.44 to 78.76 % respectively with the highest values in TL 80 and the lowest in TL 258. Variety had a significant effect on chemical compositions, GP, CH4 production, ME and OMD of grain. There is considerable amount of variation among oat varieties in terms of chemical compositions, gas production, CH4 production, ME and OMD of oat grain.  The oat grains from different varieties had provided new raw materials with a range of nutritional characteristics and will provide not only energy and protein but also fiber for ruminant animals.  Based on the chemical composition and fermentation parameters, variety TL 80 can be recommended for grain production since it has a high CP, ME and OMD.